Effects of memorable tourism experiences as mediators on visits to Mulu National Park Sarawak, Malaysia - Mahdzar, Mazlina (2016)
Tourism experience at a destination is a powerful driver of future behaviour because it determines satisfaction and memorable experience. Studies have shown that satisfying tourism experience alone is not sufficient for tourist to remain loyal to a destination as statistics on Mulu National Park shown they switched to alternative parks. Furthermore, previous research conducted in Mulu National Park, were done on satisfaction but not on experience. This study had identified factors of Memorable Tourism Experience (MTE) which is unique to Mulu National Park, Sarawak. The study further examines the impact of perceived quality, destination attributes on tourist memorable tourism experiences and their revisit intentions. A total of 349 questionnaires were collected with convenience sampling and used in the analysis. AMOS 21 was utilized to examine the psychometric properties of the model via confirmatory factor analysis (CFA) and test the hypothesized theoretical relationships of the model through structural equation modeling (SEM). The result indicates perceived quality significantly impact tourists memorable tourism experiences but not on their intentions to revisit. However, results for destination attributes significantly impact both tourists’ memorable tourism experiences and their intentions to revisit and recommend Mulu National Park. Therefore it can be concluded that memorable tourism experiences are mediator linking the relationship between both destination attributes and intentions to revisit and between perceived quality and revisit intentions. Hence, nature-based tourism marketers should design, manage and stage the experiential offering to enhance park tourists’ experiences. Moreover, the national park itself offers experiences that are unique and memorable that is observed to be the most significant dimensions of tourists experience. Park destination management should also focus on the additional facilities and services and ensure that the provision of learning and educational opportunities at the site so that the motivation experiences of nature-based tourists is fulfilled.